(untitled) (International Journal of Applied Research in Management and Economics, 2021)
This study examines, based upon four guiding research questions, how change towards a post-growth society can take place and what consequences this will have for society, i.e. as well the individual consumer, but especially for luxury as a concept and the luxury market as purveyor of goods considered luxurious. In a mixed-method approach, expert opinions, collected via qualtiative interviews, and consumer perceptions, collected via a quantitative online survey, are analyzed joinedly. The results of a content analysis and statistical tests indicate that the change to a post-growth society does not necessarily have to be accompanied by a decline in consumption, even if the majority of consumers would be prepared to support such a decline, at least to a limited extent, in order to improve the overall social situation. Whether luxury or the luxury market has a right and a potential to exist in a post-growth society can also be confirmed, whereby it is clearly emphasized that a change of today’s luxury companies towards more sustainable and resource-saving business models is essential to not become obsolete in a post-growth society.